Tarjamah , Tafsir , Takwil , dan Kriteria Mufasir - Dinda Silvy Faradila; Achmad Nabil Nur Wahid; Hakmi Hidayat (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
The Al-Qur'an, which was originally revealed in Arabic, has the perception that the Al-Qur'an is difficult for non-Arabs to understand. So in the process of learning and understanding the Al-Qur'an, several methods are put forward to support or make it easier to understand the contents of the Al-Qur'an. Tarjamah, tafsir, and takwil make it easier to understand the contents of the Al-Qur'an. These three things have something in common, namely as a means of studying and understanding the Koran. It is important to know that the Qur'an has a very broad meaning if we have the will to study its contents and contents. So, studying the Qur'an with these three methods can help us as a community who are still new to matters related to the Qur'an. Apart from that, the knowledge in tarjamah, takwil, and tafsir has been put forward by scholars who are experts in these fields. Some examples of tafsir books that are well known among the Islamic community are "Tafsir Al-Jalalain" by Sheikh Jalalludin Abu Abdillah Muhammad bin Syihabbudin Ahmad Al-Mahalli and "Tafsir As-Suyuthi" by Imam Jalaluddin As-Suyuthi. Studying the Sciences of the Qur'an is a must for the Islamic community, because the Qur'an is a guide to life that will lead to truth if we can understand and carry out what is prescribed in it. So, studying the Qur'an with these three methods can help us as a community who are still new to matters related to the Qur'an. Apart from that, the knowledge in tarjamah, takwil, and tafsir has been put forward by scholars who are experts in these fields. Some examples of tafsir books that are well known among the Islamic community are "Tafsir Al-Jalalain" by Sheikh Jalalludin Abu Abdillah Muhammad bin Syihabbudin Ahmad Al-Mahalli and "Tafsir As-Suyuthi" by Imam Jalaluddin As-Suyuthi. Studying the Sciences of the Qur'an is a must for the Islamic community, because the Qur'an is a guide to life that will lead to truth if we can understand and carry out what is prescribed in it. Apart from the importance of learning the Qur'an, the presence of a role model or someone who can be trusted in teaching this knowledge is also very important. In the science of exegesis, interpreters are known as mufasir. Because the science of tafsir is very deep and important to know, the mufasir must have characteristics that can make him a criterion for being a mufasir